2013
DOI: 10.1042/bj20130026
|View full text |Cite
|
Sign up to set email alerts
|

The P-body component USP52/PAN2 is a novel regulator of HIF1A mRNA stability

Abstract: HIF1A (hypoxia-inducible factor 1α) is the master regulator of the cellular response to hypoxia and is implicated in cancer progression. Whereas the regulation of HIF1A protein in response to oxygen is well characterized, less is known about the fate of HIF1A mRNA. In the present study, we have identified the pseudo-DUB (deubiquitinating enzyme)/deadenylase USP52 (ubiquitin-specific protease 52)/PAN2 [poly(A) nuclease 2] as an important regulator of the HIF1A-mediated hypoxic response. Depletion of USP52 reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…On the other hand, HIF‐1 is degraded under prolonged hypoxia (Millonig et al ., ). We found that chemical hypoxia decreased HIF‐1α mRNA, in agreement with data previously reported for other cell types (Uchida et al ., ; Bett et al ., ). We also observed that chemical hypoxia induced a rapid stabilization of HIF‐1α protein and a weak increase in HIF‐1α mRNA levels at very early times, after the addition of CoCl 2 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HIF‐1 is degraded under prolonged hypoxia (Millonig et al ., ). We found that chemical hypoxia decreased HIF‐1α mRNA, in agreement with data previously reported for other cell types (Uchida et al ., ; Bett et al ., ). We also observed that chemical hypoxia induced a rapid stabilization of HIF‐1α protein and a weak increase in HIF‐1α mRNA levels at very early times, after the addition of CoCl 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that ANDV infection may alter hypoxia-directed REDD1 induction, stability, or TSC1/TSC2 regulation, which normally inhibits mTOR activation (45,61,62,69). A suggested role for the hantavirus N protein in altered P-body-directed microRNA responses (65,(93)(94)(95) may contribute to this pathway activation, since microRNA levels altered by hantavirus infection regulate pathways that activate TORC1 and stabilize HIF1␣ (93,94,96). Alternatively, ANDV-altered hypoxic responses could be the result of ANDV effects on a variety of pathways that impact mTOR (31,61,69,89).…”
Section: Discussionmentioning
confidence: 99%
“…However, Edc3 has an additional structural role in the assembly of cytoplasmic foci of mRNA and proteins involved in mRNA degradation in other contexts (Decker et al, 2007; Teixeira and Parker, 2007). These structures, termed cytoplasmic processing bodies (P bodies), contain the Ccr4/Not and Pan2/3 deadenylase complexes in addition to decapping factors (Bett et al, 2013; Cougot et al, 2004; Teixeira and Parker, 2007). Cytoplasmic mRNA decay is thought to occur within P bodies since they contain decaying mRNA (Sheth and Parker, 2003).…”
Section: Introductionmentioning
confidence: 99%